Membangun Komunikasi Efektif Antara Pendidik Dengan Peserta Didik Dalam Perspektif Islam - Aminah, Siti (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2013)
Teacher who able to effective communication with student, of course they will optimize the effectiveness of their job gives instruction to the student become the faithful man. Al-Qur’an and Al-hadith as the guidance of human discusses clearly how to make effective communication. Effective communication is communication which is use good language both of verbal and nonverbal appropriate with the situation and condition so the purpose of communication will be achieved. Model of Teacher Communication that explain in Al-Qur’an are: 1) Qaulan Balighan: the model of teacher communication to touch cognitive and affective aspect of student, 2) Qaulan layyinan: flxible communication model of teacher for student who have bad character, 3) Qaulan Ma’rufa: the model of teacher communication with student as their parents, 4) Qaulan Maisuran: the model of teacher communication who has been unable to fulfil the demand of students who fid diffiulty, 5) Qaulan Karima: model of teacher communication with someone who are older or higher status, 6) Qaulan Sadida: model of teachercommunication remind the students emphatically. Prophet Muhammad SAW as the teacher has good communication therefore acceptable by His Ummah and followed all his deeds and says. The best teachers are teachers who areable to provide the best educational method which is able to communicate with the students using best way of communication.Keywords: Effective Communication, Teacher, Student, Islam.